The Influence of Minimalist Design Elements on Visual Preferences of Generation Z: A Quantitative Study - Wibowo, Mars Caroline; Zainudin, Ahmad; Sugiarto, Sugiarto (International Journal of Graphic Design, 2024)
Minimalist design has become a dominant trend across various visual media, from digital advertising to mobile applications. Generation Z, as digital natives with high exposure to visual content, exhibits unique preferences toward minimalist design. However, limited research has focused on identifying which elements of minimalist design most influence their visual preferences. This study aims to analyze the impact of key minimalist design elements—white space, simple typography, neutral colors, and layout—on the visual preferences of Generation Z. A quantitative approach was adopted using a survey-based methodology. The study involved 200 respondents from Generation Z in Indonesia, selected through purposive sampling. The research instrument was a questionnaire employing a 5-point Likert scale to measure preferences for each minimalist design element. The collected data were analyzed using descriptive statistics and regression analysis to identify the most influential elements. The findings reveal that white space is the most influential element for Generation Z, with an average score of 4.3 and a regression coefficient of 0.45 (p < 0.01). Neutral colors and simple typography also show significant impacts, with coefficients of 0.32 (p < 0.05) and 0.28 (p < 0.05), respectively. Conversely, layout demonstrated the least influence, with a coefficient of 0.15 (p > 0.05). These results confirm that Generation Z favors clean, simple, and focused designs that effectively use white space and calming color palettes. This study contributes to the graphic design literature by offering insights into the visual preferences of Generation Z. Practically, the findings provide actionable guidelines for graphic designers to create more effective digital campaigns targeting young audiences. Future research is recommended to explore cross-cultural variations in visual preferences and the role of specific media platforms in shaping these preferences.